علاقة الظروف الأسرية بارتكاب جرائم الاعتداء في المجتمع الجزائري - وصيف البيز حورية (Universty Of El-oued جامعة الوادي, 2026)
الملخص: سعت هذه الدراسة إلى استقصاء العلاقة بين الظروف الأسرية وارتكاب جرائم الاعتداء في المجتمع الجزائري، من خلال طرح التساؤل الرئيسي التالي: هل للظروف الأسرية علاقة بارتكاب جرائم الاعتداء في المجتمع الجزائري؟ ويندرج ضمن هذا التساؤل مجموعة من التساؤلات الفرعية من أبرزها: ما طبيعة جرائم الاعتداء المرتكبة في المجتمع الجزائري من طرف المودعين بالمؤسسة العقابية وموقف أسرهم من ذلك؟ هل للعلاقات الأسرية علاقة بارتكاب جرائم الاعتداء في المجتمع الجزائري؟ هل للظروف الاقتصادية علاقة بارتكاب جرائم الاعتداء في المجتمع الجزائري؟ هل للظروف السكنية علاقة بارتكاب جرائم الاعتداء في المجتمع الجزائري؟ وتماشيا مع طبيعة الموضوع فقد اعتمدت الدراسة منهجا سوسيولوجيا وصفيا تحليليا لجمع البيانات مستخدمين أداة الاستمارة كأداة رئيسية، حيث طبقت على عينة قصدية من مرتكبي الجرائم الذين تم تنفيذ حكم قضائي نهائي ضدهم، وقدر عددهم بـ (131) من مجموع (338) مفردة. أظهرت هذه الدراسة نتائج هامة منها: إن موقف أسر المبحوثين كان يميل نحو الرفض والإقصاء والتهميش، كما أظهرت بعض الأسر تواطؤا ضمنيا من خلال تقبل سلوكيات أفرادها أو ممارسة أشكال تعنيف ضدهم، وأن التهميش الاجتماعي والتمييز الذي يشعر به بعض المبحوثين ساهم في تكوين نزعة عدائية ترجمت إلى ممارسة أعمال إجرامية. هناك علاقة بين الظروف الأسرية واحتمالية ارتفاع ارتكاب جرائم الاعتداء في المجتمع الجزائري، فعلى مستوى العلاقات الأسرية تبين أن ضعف الروابط الأسرية والاجتماعية وقلة الحوار وغياب التواصل الفعّال بين أفراد الأسرة إضافة إلى استخدام أساليب المفاضلة والتمييز بين الأبناء والإهمال والمعاملة الخاطئة وغياب الرقابة الأسرية وفقدان الاحتواء في أساليب التنشئة، كلها عوامل خصبة تدفع إلى ارتكاب جرائم الاعتداء وانتشارها، وهذا ما تناولته الدراسة في محور العلاقات الأسرية وارتكاب جرائم الاعتداء في المجتمع الجزائري في الأسئلة المطروحة على مفردات الدراسة. أما على المستوى الاقتصادي فقد برزت البطالة والفقر وتدني الدخل الفردي كعوامل ضاغطة تعمّق الشعور بالإقصاء والتهميش وغياب العدالة الاجتماعية مع عدم وجود رقابة، يدفع البعض إلى اللجوء إلى ممارسة الأفعال الاجرامية الغير مشروعة كرد فعل اجتماعي تجاه هذه الظروف، وهذا ما تم تناوله في محور الظروف الاقتصادية وارتكاب جرائم الاعتداء في المجتمع الجزائري في الأسئلة المطروحة على مفردات الدراسة. وعلى الصعيد السكني فإن الإقامة في مساكن غير ملائمة ضمن أحياء متدهورة تعاني الإهمال العمراني والاجتماعي وغياب المرافق الضرورية التي تحيل دون وجود راحة وخصوصية مستقلة يفاقم من المشكلات الاجتماعية التي تقود إلى ارتكاب الأفعال الاجرامية، وهذا ما تم تناوله في محور الظروف السكنية وارتكاب جرائم الاعتداء في المجتمع الجزائري في الأسئلة المطروحة على مفردات الدراسة. خلصت الدراسة إلى أن معالجة ظاهرة جرائم الاعتداء تتداخل فيها جملة من الظروف الأسرية الكامنة التي لا يمكن أن تتم بمعزل عن تفكيكها سواء كانت مرتبة بالعلاقات الأسرية والاقتصادية والسكنية أو غيرها، وقدمت في ختامها مجموعة من التوصيات والمقترحات الموجه للأسرة ولمختلف المؤسسات التربوية والاجتماعية وصناع القرار، بهدف التقليل من تفشي وتنامي هذه الظاهرة. Abstract: This study aimed to investigate the relationship between family circumstances and the commission of assault crimes in Algerian society, by posing the following main question: Are family circumstances related to the commission of assault crimes in Algerian society? This main question encompasses a number of sub-questions, most notably: What is the nature of the assault crimes committed in Algerian society by those incarcerated in the penal institution, and what is the position of their families regarding this? Do family relationships have a connection to the commission of assault crimes in Algerian society? Are family relationships related to the commission of assault crimes in Algerian society? Are economic circumstances related to the commission of assault crimes in Algerian society? In line with the nature of the topic, the study adopted a descriptive-analytical sociological approach to data collection, using a questionnaire as the primary instrument. The questionnaire was administered to a purposive sample of (131) offenders against whom a final court ruling had been executed, out of a total of (338) individuals. This study revealed several important findings, including: The attitudes of the respondents' families ranged from rejection and exclusion to marginalization. Some families also demonstrated tacit complicity by accepting the behavior of their members or by perpetrating forms of violence against them. Furthermore, the social marginalization and discrimination felt by some respondents contributed to the development of an aggressive tendency that translated into criminal acts. There is a relationship between family circumstances and the likelihood of increased assault crimes in Algerian society. At the level of family relationships, it was found that weak family and social bonds, limited dialogue, and the absence of effective communication among family members, in addition to the use of favoritism and discrimination among children, neglect, mistreatment, lack of parental supervision, and a lack of inclusion in upbringing methods, are all fertile grounds for the commission and spread of assault crimes. This is what the study addressed in the section on family relationships and the commission of assault crimes in Algerian society, through the questions posed to the study participants. On the economic level, unemployment, poverty, and low per capita income have emerged as pressing factors that deepen feelings of exclusion, marginalization, and a lack of social justice. This, coupled with the absence of oversight, pushes some to resort to illegal and criminal acts as a social reaction to these conditions. This was addressed in the section on economic conditions and the commission of assault crimes in Algerian society, as reflected in the questions posed to the study's participants. Regarding housing, living in inadequate dwellings within dilapidated neighborhoods suffering from urban and social neglect and lacking essential amenities, which prevents comfort and privacy, exacerbates social problems that lead to the commission of criminal acts. This was also addressed in the section on housing conditions and the commission of assault crimes in Algerian society, as reflected in the questions posed to the study's participants. The study concluded that addressing the phenomenon of assault crimes involves a number of underlying family circumstances that cannot be addressed in isolation from their dismantling, whether they are related to family, economic, housing, or other relationships. In conclusion, it presented a set of recommendations and proposals directed to the family, various educational and social institutions, and decision-makers, with the aim of reducing the spread and growth of this phenomenon.
- دراسة ميدانية بولاية الوادي -
Keywords: الأسرة، الظروف الأسرية، الجريمة، جرائم الاعتداء.; Family; family circumstances; crime; assault crimes.